Conditional same/different concept learning in the short‐beaked echidna (Tachyglossus aculeatus). Issue 1 (18th January 2016) - Russell, Fiona; Burke, Darren
Abstract : Echidnas have evolved separately from other mammalian groups for around 200 million years and incorporate a mixture of reptilian and mammalian features. Because of these attributes, they have historically been considered "primitive" animals. However, they have successfully adapted to a wide variety of ecological niches and their neurophysiology demonstrates a number of unusual and apparently sophisticated characteristics, including a relatively large brain and cerebral cortex and a comparatively massive frontal cortex. Studies of learning in the echidna have thus far been limited to only a handful of experiments which demonstrated relatively basic abilities such as forming a position habit in a T‐maze, successive habit‐reversal learning, and simple visual and instrumental discrimination. This study aimed to expand on these results and test the "primitive" echidna on what are generally considered more advanced cognitive tasks—same/different and conditional same/different concept learning. The results demonstrated that echidnas are able to discriminate on the basis of a relational same/different concept, using simultaneously presented multi‐element stimuli, and transfer that discrimination to novel stimuli. After further training, they were then able to repeat the performance when the correct choice was conditional on the background color of the stimulus panels.